Pentingnya Strategi Bisnis Yang Tepat Dalam Mempertahankan Eksistensi Suatu Usaha (Studi Kasus: Penutupan Sevel) - Ari Yuliani; Eko Harry Susanto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Sevel is a well known brand for convinience store that has thousand outlets in seventeen countries. In June 2018 Sevel had to stop their business in Indonesia due to the buyout failure by Charoen Pokphand. Sevel should have still operate their business as they have strong management and infrastructure to do so. The purpose of this study is to examine whether the business strategies they had been running for is the right strategies and if its not, what kind of strategies should be applied for the company business. The analysis methods of this research use five matrix, i.e Internal Factor Evaluation (IFE) Matrix, Eksternal Factor Evaluation (EFE) Matrix, Competitive Profil Matriks (CPM), SWOT Matrix, SPACE Matrix, Internal Eksternal (IE) Matrix and QSPM. The QSPM matrix result shows that Sevel should focus on market penetration strategy in 2016 as there were so many factors, either form internal or eksternal environment, to support their action plan while they still can run few strategies from retrenchement strategy as necessary.